2019
DOI: 10.1021/acs.jpclett.9b02488
|View full text |Cite
|
Sign up to set email alerts
|

Band Alignment Engineering between Planar SnO2 and Halide Perovskites via Two-Step Annealing

Abstract: Managing defects in SnO2 is critical for improving the power conversion efficiency (PCE) of halide perovskite-based solar cells. However, typically reported SnO2‑based perovskite solar cells have inherent defects in the SnO2 layer, which lead to a lower PCE and hysteresis. Here, we report that a dual-coating approach for SnO2 with different annealing temperatures can simultaneously form a SnO2 layer with high crystallinity and uniform surface coverage. Along with these enhanced physical properties, the dual-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
(51 reference statements)
3
19
0
Order By: Relevance
“…25 Yip et al presented a dramatic enhancement of V OC in PSCs with the introduction of the SnO 2 /ZnO bilayer; 26 the favorable energy level improved the charge extraction and suppressed the interfacial recombination. Lee et al demonstrated a dual-coating method to deposit SnO 2 film at different annealing temperatures, 27 which leads to better energy level alignment with the perovskite layer and thus resulted in improved PSCs performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Yip et al presented a dramatic enhancement of V OC in PSCs with the introduction of the SnO 2 /ZnO bilayer; 26 the favorable energy level improved the charge extraction and suppressed the interfacial recombination. Lee et al demonstrated a dual-coating method to deposit SnO 2 film at different annealing temperatures, 27 which leads to better energy level alignment with the perovskite layer and thus resulted in improved PSCs performance.…”
mentioning
confidence: 99%
“…As per the previous report, hydroxyl groups exist on the surface of SnO 2 and can bind to metal sites. 27 There are two main active sites on the surface of the SnO 2 crystal, which could interact with water to form a hydroxyl group, a more hydroxylated surface when treated with UV-ozone. The defect sites (hydroxyl group) would lead to a trap state and cause nonradiative recombination.…”
mentioning
confidence: 99%
“…Compared with ZnO and TiO 2 , SnO 2 is an n‐type semiconductor material with a wide bandgap, high transmittance, strong electron mobility, and high chemical stability. [ 97–100 ] Recently, the development of PSCs based on SnO 2 as an ETL has been very rapid, especially under the guidance of You's research group, which achieved commercial high‐quality SnO 2 film. [ 101,102 ] SnO 2 has a wider bandgap, which not only absorbs less UV light but also owns excellent chemical stability.…”
Section: Preparation and Characteristics Of Electron Transport Materialsmentioning
confidence: 99%
“…However, most of the devices based on low-temperature solution-processed SnO 2 were reported to suffer from serious photocurrent hysteresis which makes it difficult to determine their real PCEs. 103,104 The optoelectronic properties of n-type semiconducting ZnO, such as a suitable conduction band energy level (BÀ4.17 eV for the CBM), large optical bandgap of 3.3 eV, high electronic mobility and high transmittance, are promising for applications in PSCs. [105][106][107] In addition, the low-temperature processed ZnO nanocrystalline thin films are favourable for flexible devices.…”
Section: Electron Transport Materials In Pscsmentioning
confidence: 99%